2017
DOI: 10.1186/s40497-017-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the factors affecting social entrepreneurial intentions

Abstract: The present study aims at identifying the social entrepreneurial intention among undergraduate students in Indian context by using the theory of planned behaviour as the research framework. A 72 item questionnaire was responded by 390 students of premier technical universities of India. A method of sampling used was systematized random sampling. 69% (N = 269) of the respondents were male and 31% (N = 121) were female and the average age of the respondents was approximately 20 years. The questionnaire measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 94 publications
(126 reference statements)
6
116
0
15
Order By: Relevance
“…Previous studies have already confirmed that the three attitudinal antecedents are also capable of explaining the appearance of sustainable entrepreneurial intention [24][25][26][27][28]. Therefore, building on the TPB and a sample of 175,280 respondents, an intention-based framework is developed to empirically investigate the impact of environmental risk exposure on the formation of sustainable entrepreneurial intention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already confirmed that the three attitudinal antecedents are also capable of explaining the appearance of sustainable entrepreneurial intention [24][25][26][27][28]. Therefore, building on the TPB and a sample of 175,280 respondents, an intention-based framework is developed to empirically investigate the impact of environmental risk exposure on the formation of sustainable entrepreneurial intention.…”
Section: Introductionmentioning
confidence: 99%
“…These results coincide with those of Ajzen, (1998Ajzen, ( ,1991Ajzen, ( ,2002Fisbein and Ajzen, (1975);Guido et al, (2011);Liñan and Chan (2009);Rhodes and Courneya, (2003);Scholten, Kemp and Omta, (2004);Schwarz, et al, (2009);Shook and Britanu, (2010);Solvesik et al, (2012);and Tkachev and Kolvereid, (1999), where in their studies the positive effect between subjective norm and entrepreneurial behavior is considered. However, this does not happen with India, adding to the pool of other studies that have not found a significant relationship between subjective norm and intention (Autio, et al, 2001;Krueger et al, 2000;& Liñán, 2008, Tiwari, Bhat & Tikoria 2017). This study was also able to determine that the total indirect effect is higher than the direct effect in the countries at study, with the exception of Portugal.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In some cases, may even extend to the point of illiteracy (Shaw & de Bruin, 2013), however, it has a Total of Entrepreneurial Activity (TEA) of 10.6, matching competitively with other countries of Asia and Oceania (GEM, 2016). Considered a country with noticeable collectivist values, Tiwari, Bhat and Tikoria (2017) found a significant relationship between its subjective norm and entrepreneurial intention. Similarly, a study by Iakovleva, Kolvereid, and Stephan (2011), investigated the relationship of entrepreneurial intention between emerging and developed countries, which India participated, demonstrating that the relationship of attitudes and perceived control have less intensity in entrepreneurial intention within developing countries than in developed ones.…”
Section: Introductionmentioning
confidence: 99%
“…If emphasizing entrepreneurship in the Philippines' educational landscape is vital (Lacap, 2017), then it is also important that emphasis is placed on social entrepreneurship. Social entrepreneurs are considered agents of change and are individuals who can give solutions to pressing issues in the society in more creative and innovative ways (Tiwari, Bhat, & Tikoria, 2017), thus measuring social entrepreneurial intentions of people can provide vital information on how to come up with more social entrepreneurship researches particularly in the Philippines.…”
Section: Discussionmentioning
confidence: 99%